Meal replacements as a strategy for weight loss in obese hemodialysis patients. Issue 4 (4th April 2016) - Lassemillante, Annie‐Claude M.; Oliver, Veronica; Hickman, Ingrid; Murray, Eryn; Campbell, Katrina L.
Abstract: Introduction There is currently limited evidence on the use or safety of meal replacements as part of a low– or very–low‐calorie diet in patients with renal insufficiency; however, these are occasionally used under dietetic supervision in clinical practice to achieve the desired weight loss for kidney transplant. This case series reports on the safety and efficacy of a weight loss practice utilizing meal replacements among hemodialysis patients, who needed to lose weight for kidney transplant. Methods Five hemodialysis patients were prescribed a modified low‐calorie diet (950 kcal and 100 g protein per day) comprising three meal replacements (Optifast ® ), one main meal, and two low‐potassium fruits per day. Dietary requirements and restrictions were met for all participants. Dialysis prescriptions, weight (predialysis and postdialysis), interdialytic weight gain, biochemistry, and medications were monitored during the study period for up to 12 months. Findings Participants were aged between 46 and 61 years, and the median time on the low‐calorie diet was 364 days. Phosphate binders were temporarily ceased for one participant for reasons unrelated to this program and no other safety concerns were recorded. The low‐calorie diet resulted in energy deficits ranging from 1170 kcal to 2160 kcal, and all participants lost weight (median 7% [range 5.2%–11.4%]). The most dramatic weight change appeared to occur by week 12, and declining adherence led to erratic weight change thereafter. Discussion This modified low‐calorie diet was safe and effective to use in this population. Meal replacements are a useful weight loss strategy in hemodialysis patients, therefore, offering an alternative to usual weight loss protocols.